The history of post-war Southeast Asia : - Cady, John Frank (Ohio University Press, 1974)
Contents: This is the fisrt full-scale history of Southeast Asia which covers the period from 1945 to the present. It commplements the author's earlier book, entitled Southeast Asia: Its Historical Development. Although there are other collections of essays on individual countries in Southeast Asia, the single-author study offers a cohesive approach which brings the total area into better focus. Dr. Cady's study is valuable in a comparative sense.